The Evolution of Strategic Management Research: Recent Trends and Current Directions*. Issue 2 (April 2014) - Guerras-Martín, Luis Ángel; Madhok, Anoop; Montoro-Sánchez, Ángeles
Strategic management is a relatively youthful discipline that has steadily matured over the past fifty years. The field has become consolidated over this period, while simultaneously expanding the range of topics analyzed and research methodologies used. Different theories and approaches, addressing different research topics, have been developed to explain the reasons underlying firms' competitive advantage and success. In this paper, we posit the existence of two pendulums in constant motion that, on the one hand, reflect the tension that has historically existed between the focus on internal firm factors and external environmental attributes respectively and, on the other hand, the tension between a more macro level of analysis, i.e., the firm and its environment, and a more micro level one, i.e., individuals and their relations within the firm. The frontier of research in strategic management is shaped by the simultaneous movement of both pendulums.